Personality or individuality: whoa are needed for modern society? - Podshyvalkina, Valentine (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article proves the thesis about the civil society as the society of individualities. It is shown that the mechanism of formation of individuality is the exteriorization process of human's inner potential and his impact on society. Criteria for the existence of individuality as a dynamic phenomenon are proposed, such as: time, plurality, integrity and social effects. The genesis of the requirements of society to a person in the last two centuries was shown. The necessity in today's labor market in different types of human potential and its usage trends, such as: "a unique specialist," "self-sufficient person", "good people", "white sheets" is empirically grounded. The empirical results showed that there are two subtypes of the capacity of self-development: active and passive. In the first subtype – person acts as the subject of self-development, and in the other – as the object for external influences. We also showed trends in the development of professional groups, which are expressed in the requirements for the integrity of the manifestations individual's qualities, individual characteristics, and that the development of these professional activities depends on the individuality of professionals, their creativity.
Keywords: self-realization; self-development; personality; individuality